Long noncoding RNA LINC00239 inhibits ferroptosis in colorectal cancer by binding to Keap1 to stabilize Nrf2 - Han, Yuying; Gao, Xiaoliang; Wu, Nan; Jin, Yirong; Zhou, He; Wang, Weijie; Liu, Hao; Chu, Yi; Cao, Jiayi; Jiang, Mingzuo; Yang, Suzhen; Shi, Yanting; et al. (Cell death & disease, 2022)
Ferroptosis, a novel regulated cell death induced by iron-dependent lipid peroxidation, plays an important role in tumor development and drug resistance. Long noncoding RNAs (lncRNAs) are associated with various types of cancer. However, the precise roles of many lncRNAs in tumorigenesis remain elusive. Here we explored the transcriptomic profiles of lncRNAs in primary CRC tissues and corresponding paired adjacent non-tumor tissues by RNA-seq and found that LINC00239 was significantly overexpressed in colorectal cancer tissues. Abnormally high expression of LINC00239 predicts poorer survival and prognosis in colorectal cancer patients. Concurrently, we elucidated the role of LINC00239 as a tumor-promoting factor in CRC through in vitro functional studies and in vivo tumor xenograft models. Importantly, overexpression of LINC00239 decreased the anti-tumor activity of erastin and RSL3 by inhibiting ferroptosis. Collectively, these data suggest that LINC00239 plays a novel and indispensable role in ferroptosis by nucleotides 1–315 of LINC00239 to interact with the Kelch domain (Nrf2-binding site) of Keap1, inhibiting Nrf2 ubiquitination and increasing Nrf2 protein stability. Considering the recurrence and chemoresistance constitute the leading cause of death in colorectal cancer (CRC), ferroptosis induction may be a promising therapeutic strategy for CRC patients with low LINC00239 expression.